Socio-Psychological Predictors of Successful Integration of Institutionalized Adolescents into Mainstream Schools - Elena V. Bakhvalova; Anastasia V. Miklyaeva (National Research Mordova State University, 2021)
Introduction. The study sought to reveal socio-psychological factors of successful integration of institutionalized adolescents into mainstream schools. The relevance of the research is determined by the necessity to spread practices of integrating institutionalized children and adolescents into mainstream schools to expand their social experience. Materials and Methods. The purpose of the study was to explore the socio-psychological predictors that determine the successfulness of integration of institutionalized adolescents into mass secondary schools. Among the sociopsychological predictors of integration success, we analyzed the communicative characteristics of adolescents and the specifics of their relations with other subjects of the educational process. The study involved 678 people including students of secondary schools with integration programs, their parents and teachers. The empirical data were collected through questionnaires, expert survey of teachers, and projective drawing with subsequent expert evaluation of the results, as well as testing, including M. Kondash' Anxiety Scale (to assess the adaptation of orphaned children in school), S. Bratchenko's methods "Direction of the personal communication", M. Snyder's Diagnostics of communicative control (to assess their communicative potential) and J. Moreno's Sociometry (to assess their place in the system of interpersonal relations with classmates). Results. The results show that about one out of ten institutionalized adolescents successfully integrates into the educational process of mainstream schools, while the others experience difficulties in this process. Significant predictors of successful integration are indicators that characterize the communication skills of institutionalized adolescents, as well as their relationships with "adult" subjects of the educational process (primarily, parents of classmates). The most favorable conditions for the successful integration of institutionalized adolescents into mainstream schools are associated with the first stages of their attendance at a mainstream education institution. Discussion and Conclusion. The findings contribute to social and educational psychology and can be used to develop scientifically-based system of social-psychological support of integration of institutionalized adolescents into mainstream schools, the targets which should be aimed at the development of communicative skills of institutionalized adolescents, and also on formation of system of their relations with other subjects of educational process.